The Implementation of Inquiry Method to Increase Students’ Participation and Achievement in Learning Social Studies - Agustina Tyas Asri Hardini (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2017)
This research was conducted to increase students’ participation and achievement in learning Social Studies of grade 4 by implementing inquiry method in SD Negeri Kenteng 1 Kecamatan Susukan Kabupaten Semarang semester II year 2016/2017. This research was based on Kemmis and Taggart classroom action research model. The subject of this study were 17 students. The indicator of success of this study was that 80% of the students achieve equal or more than the passing grade (70). It was shown that the implementation of inquiry method is able to increase students’ participation and achievement. The ratio of participation from phase 1 to phase 2 increased from 64.70% to 88.23%. On the other side, students’ achievement in phase 1 was that 70.50% of the students reached the minimum passing grade with the mean value of 88.90. On the second phase, 100% of the students were able to pass the minimum passing grade, and the mean value of the class increase to 93.80. From those result, it can be stated that inquiry method was able to increase students’ participation and achievement in learning Social Studies for grade 4 students of SD Negeri Kenteng 1 Kecamatan Susukan Kabupaten Semarang.